Real-Time Threat Detection for Women - VishnuPriya A.V,; Deekshi S,; Gowthami M,; Kanivarshini N,; Dharani Priyan E, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Women’s safety has become a crucial concern, demanding innovative technological solutions for real-time protection. This paper proposes an IoT-based Women Safety System designed to enhance personal security and provide immediate assistance in emergencies. The system employs an ESP32-CAM to capture and store images on Google Drive, ensuring visual evidence is available. An Arduino Uno is integrated with a PIR motion sensor for movement detection and a sound sensor to recognize distress signals. Additionally, a NEO-6M GPS module enables real-time location tracking, while a GSM module automatically sends SOS alerts with GPS coordinates to pre-defined emergency contacts. The combination of hardware and software automation ensures that women in distress can seek help instantly, minimizing response time. The system is compact, portable, and easy to carry, making it highly practical for everyday use. Furthermore, the data stored on cloud platforms enhances future investigation processes by providing authentic evidence. This research emphasizes the role of IoT in empowering women through advanced safety measures, reducing crime rates, and promoting a secure environment.
Keywords: Women Safety; IoT; ESP32-CAM; Arduino Uno; PIR Motion Sensor; Sound Sensor; NEO-6M GPS Module; GSM Module; Real-Time Monitoring; SOS Alert; Emergency Response; Google Drive Integration; Embedded Systems; Smart Security; Threat Detection; Location Tracking; Automated Safety System; Personal Security; Wireless Communication